A Real-Time PCR Assay for the Diagnosis of Intestinal Schistosomiasis and Cure Assessment After the Treatment of Individuals With Low Parasite Burden - Siqueira, Liliane Maria Vidal; Senra, Carolina; de Oliveira, Áureo Almeida; Carneiro, Nidia Francisca de Figueiredo; Gomes, Luciana Inácia; Rabello, Ana; Coelho, Paulo Marcos Zech; Oliveira, Edward (Frontiers in Immunology, 2021)
The laboratorial diagnosis of the intestinal schistosomiasis is always performed using Kato-Katz technique. However, this technique present low sensitivity for diagnosis of individuals with low parasite burden, who are mostly present in low endemicity Brazilian locations for the disease. The objective of this study was develop and to validaty a real-time PCR assay (qPCR) targeting 121 bp sequence to detect Schistosoma spp. DNA for the diagnosis of intestinal schistosomiasis and a sequence of the human β-actin gene as internal control. Firstly, the qPCR was stantardized and on followed it was evaluated for diagnosis and cure assessment of intestinal schistosomiasis in the resident individuals in Tabuas and Estreito de Miralta, two locations in Brazil endemic for intestinal schistosomiasis. The qPCR assay results were compared with those of the Kato-Katz (KK) test, examining 2 or 24 slides, Saline Gradient (SG) and “reference test” (24 KK slides + SG). The cure assessment was measured by these diagnostic techniques at 30, 90, and 180 days post-treatment. In Tabuas, the positivity rates obtained by the qPCR was 30.4% (45/148) and by “reference test” was of 31.0% (46/148), with no statistical difference (p= 0.91) The presumed cure rates at 30, 90, and 180 days post-treatment were 100, 94.4, and 78.4% by the analysis of 24 KK slides, 100%, 94.4%, and 78.4% by the SG, and 100%, 83.3%, 62.1% by the qPCR assay. In Estreito de Miralta, the positivity obtained by qPCR was 18.3% (26/142) and with “reference test” was 24.6% (35/142), with no statistical difference (p= 0.20). The presumed cure rates were 93.3, 96.9, and 96.5% by the KK, 93.3%, 96.9%, and 100% by the SG, and 93.3%, 93.9%, and 96.5% by the qPCR at 30, 90, and 180 days post-treatment, respectively. This study showed that the diagnositic techniques presented different performance in the populations from the two districts (Tabuas and Estreito de Miralta) and reinforces the need of combining techniques to improve diagnosis accuracy, increasing the detection of individuals with low parasite burden. This combination of techniques consist an important strategy for controlling the disease transmission.